Approaching Perfect Light Incoupling in Perovskite and Silicon Thin Film Solar Cells by Moth Eye Surface Textures. Issue 8 (21st June 2018) - Qarony, Wayesh; Hossain, Mohammad Ismail; Dewan, Rahul; Fischer, Stefan; Meyer‐Rochow, V Benno; Salleo, Alberto; Knipp, Dietmar; Tsang, Yuen Hong
Abstract: Solar cells with increased short‐circuit current density and energy conversion efficiency can be realized by integrating moth eye textures in the design of perovskite and amorphous silicon thin film solar cells. Broadband light incoupling in solar cells can be achieved by using hexagonally arranged arrays of nipples or domes with parabolically shaped surface profiles. The moth eye surface texture represents a refractive index grating that allows for an efficient incoupling of light in the solar cell while minimizing reflection losses. The light incoupling is studied for perovskite and amorphous silicon solar cells. Perovskite has a rather low refractive index of ≈2.5, while amorphous silicon exhibits a refractive index of ≈4.5 comparable to that of crystalline silicon. Due to largely different refractive indices, different device designs must be selected to allow for an efficient light incoupling in the solar cell. 3D finite‐difference time‐domain simulations are used for the optical modeling. Design guidelines are provided on how to realize perovskite and silicon thin film solar cells with high quantum efficiency and short‐circuit current by using moth eye textures. Abstract : The moth eye texture is integrated on perovskite and amorphous silicon solar cells to determine the upper limit of short‐circuit currents and energy conversion efficiency gains. Two model systems are compared, and the analytical calculations are confirmed by numerical simulations, allowing for short‐circuit current gains of 10–15% and 20–25% for perovskite and amorphous silicon solar cells, respectively.